2020
DOI: 10.5430/ijfr.v11n3p139
|View full text |Cite
|
Sign up to set email alerts
|

General Election and Stock Market Performance: A Malaysian Case

Abstract: The 2018 Malaysia general election has marked a new history for the Malaysia political structure. After more than 60 years Barisan Nasional ruling the country, in the 2018 general election Barisan Nasional lose the game to the Pakatan Harapan. The results of the 14th general election has caused a shock not only to political arena but also to the Malaysian financial market. Therefore, this paper aims to investigate if there is any significant effect of 14th Malaysia general election on the Malaysia financial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It has been reported that the net foreign fund outflow in 2018 for Malaysia totalled RM11.65 billion. 14 The last factor that adversely impacted the stock market was investor sentiment. Issues such as unresolved trade wars, lower oil prices, and geopolitical tension had refrained investors from securities investment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the net foreign fund outflow in 2018 for Malaysia totalled RM11.65 billion. 14 The last factor that adversely impacted the stock market was investor sentiment. Issues such as unresolved trade wars, lower oil prices, and geopolitical tension had refrained investors from securities investment.…”
Section: Resultsmentioning
confidence: 99%
“…Against the backdrop of Malaysia, Misman et al (2020) investigate the Malaysian stock market reactions surrounding Malaysian general elections using ordinary least squares (OLS) for election cycles from GE10 to GE14. The authors conclude that the Malaysian stock market does register substantive changes surrounding general elections.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Against the backdrop of Malaysia, Misman et al. (2020) investigate the Malaysian stock market reactions surrounding Malaysian general elections using ordinary least squares (OLS) for election cycles from GE10 to GE14.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Jha, Bhattacharya, and Bhattacharya (2019) find that a surge in Google search queries is linked to an increase in trading activity and stock liquidity in NSE. In other context, a recent study by Misman, Roslan, and Aladin (2020) state that the 14th general election in Malaysia has a significant impact on the stock market performance.…”
Section: Related Researchmentioning
confidence: 99%